A simple and versatile solvothermal configuration to synthesize superparamagnetic iron oxide nanoparticles using a coaxial microwave antenna. Issue 106 (1st November 2016) - Spepi, Alessio; Duce, Celia; Ferrari, Carlo; González-Rivera, José; Jagličić, Zvonko; Domenici, Valentina; Pineider, Francesco; Tiné, Maria Rosaria
Abstract : Magnetic iron oxide nanoparticles (IONs) with controllable physicochemical and magnetic properties were synthesized by a fast and simple solvothermal microwave (MW) assisted approach. Abstract : Magnetic iron oxide nanoparticles (IONs) with controllable physicochemical and magnetic properties were synthesized by a fast and simple solvothermal microwave (MW) assisted approach. The MW-assisted synthesis using a coaxial microwave antenna was carried out in different routes: (i) a fast one-step solvothermal approach, and (ii) a non-aqueous sol–gel system. This innovative configuration obtained IONs maghemite crystal phase, in a very short reaction time (from 5 to 15 min), with a small size (6 nm) and narrow particle size distribution. Magnetization as a function of the applied magnetic field revealed that all the samples showed superparamagnetisms, with a saturation magnetization ranging from 60 to 68 emu g −1 ( T = 300 K). TEM, XRD, FTIR, TG, and magnetic measurements were used to fully characterize the IONs. Not only did the proposed methodologies using the coaxial MW configuration produce IONs with similar or improved physicochemical and magnetic properties, but they also overcame the classical drawbacks of oven-type MW configurations.